Successful Correction of the Human Cooley's Anemia β-Thalassemia Major Phenotype Using a Lentiviral Vector Flanked by the Chicken Hypersensitive Site 4 Chromatin Insulator - MALIK, PUNAM; ARUMUGAM, PARITHA I.; YEE, JING-KUAN; PUTHENVEETIL, GEETHA (Annals of the New York Academy of Sciences, 2005)
: β‐Thalassemias are the most common single‐gene disorders and are potentially amenable to gene therapy. While retroviral vectors carrying the human β‐globin cassette were notoriously unstable and expressed poorly, considerable progress has now been made using lentiviral vectors (LVs), which stably transmit the β‐globin expression cassette. Mouse studies using LVs have shown correction of the β‐thalassemia‐intermedia phenotype and a partial, variable correction of the mouse β‐thalassemia major phenotype, despite the use of β‐globin‐hypersensitive sites that are known to result in position‐independent effects. Our group used the α‐globin‐hypersensitive site in self‐inactivating (SIN) LVs with long‐term expression in secondary mice that resisted methylation‐associated proviral silencing. However, these vectors also suffered from chromatin position effects. We therefore flanked a SIN‐lentiviral vector carrying the human β‐globin expression cassette with a chromatin insulator and studied expression in bone marrow from four patients with transfusion‐dependent human thalassemia major. We demonstrated normal levels of human β‐globin expression in erythroid cells produced in in vitro cultures for unilineage erythroid differentiation. There was restoration of effective erythropoiesis and reversal of the abnormally elevated apoptosis that characterizes β‐thalassemia. The gene‐corrected human β‐thalassemia progenitor cells were transplanted into immune‐deficient mice, where they underwent normal erythroid differentiation, expressed normal levels of human β‐globin, and displayed normal effective erythropoiesis 3‐4 months after xenotransplantation. Variability of β‐globin expression in erythroid colonies derived in vitro or from xenograft bone marrow was similar to that seen in normal control subjects. Results show genetic correction of primitive human progenitor cells and normalization of the human thalassemia major phenotype.